Organic thermoelectric devices based on a stable n-type nanocomposite printed on paper. Issue 2 (3rd November 2017) - Ferhat, Salim; Domain, Christophe; Vidal, Julien; Noël, Didier; Ratier, Bernard; Lucas, Bruno
Abstract : (PEDOT) x V2 O5 nanocomposites optimized for thermoelectric generation, adapted for the first time to printing technology and used for patterning a device. Abstract : We present a fully inkjet-printed flexible thermoelectric device using organic and organic/inorganic hybrid materials. As part of our effort in the development of an n-type material, we present an approach to synthesize a solution processable thermoelectric hybrid material based on in situ oxidative polymerization and intercalation that can yield layered quasi two-dimensional superlattice structures. Thus, we have inserted poly(3, 4-ethylenedioxythiophene) (PEDOT) within the nanotemplates of vanadium pentoxide gel (V2 O5 · n H2 O) in order to enhance the charge carrier concentration. Furthermore, for the first time, we adapted the hybrid (PEDOT) x V2 O5 material to the inkjet printing technology, thus successfully proving the printability of (PEDOT) x V2 O5 . Hence, we successfully produced a thermoelectric device composed of 4 thermocouples. Moreover, we optimized the geometry of the organic thermoelectric generator (OTEG) device thanks to a numerical model; the simulated and measured results are presented. The OTEG yielded a power density as high as 0.266 μW cm −2 for a temperature gradient of 20 K, therefore unveiling the potential of hybrid V2 O5 -based compounds for thermoelectric applications.